Relação entre cultura organizacional e processo de inovação: estudo de caso em uma empresa de tecnologia do polo digital de Manaus - Ferreira, Ana Claudete da Silveira (Brasil, 2024)
This article aims to analyze the relationship between the organizational culture and the culture of innovation in a technology company of the Manaus Digital Polo, FPFtech, which develops solutions in the area of software and hardware. The research is justified by the relevance of the theme to the technology business environment, especially in a scenario of high competitiveness and dynamism in which the area is inserted.